Perbedaan Hasil Belajar Kognitif Peserta Didik Menggunakan Model RADEC Berbantuan Zep Quiz pada Pembelajaran IPAS di Kelas IV SD - Alifia Yasmin, Putri; Amsari, Dina; Zuryanty; Amini, Risda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low cognitive learning outcomes of students in Science and Social Studies (IPAS) learning. The study aimed to determine the difference in students' cognitive learning outcomes between those taught using the RADEC learning model assisted by Zep Quiz and those taught using the conventional learning model in fourth-grade elementary school. This study employed a quantitative approach with a Quasi-Experimental Design, specifically the Nonequivalent Control Group Design. The research sample consisted of fourth-grade students of SDN 15 Koto Lalang as the experimental class and SDN 14 Koto Lalang as the control class. Data were collected through learning achievement tests and analyzed using the normality test, homogeneity test, and Independent Sample t-test on the gain scores (the difference between pre-test and post-test scores) with the assistance of IBM SPSS Statistics 30.0. The results showed that the mean post-test score of the experimental class was 87.04, while that of the control class was 80.93. In addition, students' evaluation results demonstrated continuous improvement throughout the learning process. The hypothesis test yielded a Sig. (one-sided p) value of 0.001, which was lower than the significance level of 0.05 (0.001 < 0.05). Therefore, H₀ was rejected and H₁ was accepted. It can be concluded that there was a significant difference in the improvement of students' cognitive learning outcomes between the class taught using the RADEC learning model assisted by Zep Quiz and the class taught using the conventional learning model.